A review and comparison of midwifery management and education in five representative countries - Nan Zhou; Hong Lu (Elsevier, 2018)
Midwives play an important role in guaranteeing mothers and babies' good health. However, standardisation and systematic management of midwifery are insufficient in China. This study reviews and compares the present situation of midwifery management and education in five representative countries located in North America, Europe and Oceania. Based on the experience of these countries, Midwifery development in China should continue to explore and develop midwifery university education, form a midwife professional title system, standardize midwife certification and management. And a quality midwifery environment should be created in order to enhance career attractiveness. Keywords: Education, Personnel management, Midwives